Cervical Spine Motion During Tracheal Intubation Using an Optiscope Versus the McGrath Videolaryngoscope in Patients With Simulated Cervical Immobilization: A Prospective Randomized Crossover Study. (December 2019) - Nam, Karam; Lee, Younsuk; Park, Hee-Pyoung; Chung, Jaeyeon; Yoon, Hyun-Kyu; Kim, Tae Kyong
Abstract : BACKGROUND: In patients with an unstable cervical spine, maintenance of cervical immobilization during tracheal intubation is important. In McGrath videolaryngoscopic intubation, lifting of the blade to raise the epiglottis is needed to visualize the glottis, but in patients with an unstable cervical spine, this can cause cervical spine movement. By contrast, the Optiscope, a rigid video-stylet, does not require raising of the epiglottis during tracheal intubation. We therefore hypothesized that the Optiscope would produce less cervical spine movement than the McGrath videolaryngoscope during tracheal intubation. The aim of this study was to compare the Optiscope with the McGrath videolaryngoscope with respect to cervical spine motion during intubation in patients with simulated cervical immobilization. METHODS: The primary outcome of the study was the extent of cervical spine motion at the occiput–C1, C1–C2, and C2–C5 segments. In this randomized crossover study, the cervical spine angle was measured before and during tracheal intubation using either the Optiscope or the McGrath videolaryngoscope in 21 patients with simulated cervical immobilization. Cervical spine motion was defined as the change in angle at each cervical segment during tracheal intubation. RESULTS: There was significantly less cervical spine motion at the occiput–C1 segment using the Optiscope rather than the McGrath videolaryngoscope (mean [98.33% CI]: 4.7° [2.4–7.0] vs 10.4° [8.1–12.7]; mean difference [98.33% CI]: −5.7° [−7.5 to −3.9]). There were also fewer cervical spinal motions at the C1–C2 and C2–C5 segments using the Optiscope (mean difference versus the McGrath videolaryngoscope [98.33% CI]: −2.4° [−3.7 to −1.2]) and −3.7° [−5.9 to −1.4], respectively). CONCLUSIONS: The Optiscope produces less cervical spine motion than the McGrath videolaryngoscope during tracheal intubation of patients with simulated cervical immobilization.